Hodge 53-47: An early O-type double-lined binary in the Small Magellanic Cloud - Morrell, Nidia Irene (2003)
We present a spectroscopic and photometric study of the double-lined binary Hodge 53-47 in the Small Magellanic Cloud. We determine for the binary components spectral types of O6 V + O4-5 III(f). Through a simultaneous light and radial velocity curve analysis via the Wilson-Devinney code we find absolute masses of ∼26 M⊙ and ∼ 16 M⊙ and radii of ∼ 10.1 R⊙ and ∼8.4 R⊙ for the O6 V and O4-5 III(f) components, respectively. The relatively low mass found for the O4-5 III(f) component suggests that mass transfer and loss have played a significant role in the evolution of these stars.